Effect of Topical Serratiopeptidase on Facial Wound Healing in Rabbit - Faehaa A. Al-Mashhadanee (Journal of Global Pharma Technology, 2020)
Abstract Objective: Serratiopeptidase (SRP), an enzyme with great effect in opposing inflammation. Applications of enzyme topically provide advantage of direct entery to the location of action. This study examined the possibility of using topical SRP preparations in the formula of ointments and to assess the topical effect of SRP in facial wound management in rabbits. Material and Method: healthy male rabbits weight,1.25 ± 0.25kg divided into four groups: group one animals received no treatment, group two animals treated with Vaseline only, group three and four were treated by SRP (0.5% and 1%) respectively. Standard incisions were done on submandibular region of all rabbits. Wound healing assessment was determined by histological method. Results: group one and two showed incomplete closure of the wound with poor re-epithelization, while other groups (three and four) demonstrated complete closure of the wound with good re-epithelization. Conclusion: topical application of SRP has ability to improve facial wound healing in rabbits. Keywords: Serratiopeptidase, Facial wound, Rabbit.